APPLICATION INFORMATION MEDIA PROMOTIONS PT. THE ONE USING MACROMEDIA FLASH 8.0 - Denny Affiat; Aqwam Rosadi Kardian, SKom, MM (Jurnal Sistem Informasi, 2009)
This application contains about the latest services that is owned by PT. THE ONE,the more services enable customers to use the services of PT. THE ONE, like thepages of criticism and suggestions addressed to PT. THE ONE can further improvethe services provided.This application is created using Macromedia Flash 8.0, so these applications aredynamic, and more interactive in its use.